Effects of Heat Stress at Vegetative and Reproductive Stages on Spikelet Fertility - Sulaiman Cheabu; Peerapon Moung-Ngam; Siwaret Arikit; Apichart Vanavichit; Chanate Malumpong (Rice Science, 2018)
Seed-setting rate, yield components and grain quality traits of 169 accessions from an exotic rice germplasm were tested under high temperatures from 40 °C to 45 °C for 6 h during the daytime at the vegetative and reproductive stages, respectively. The results showed that heat stress significantly decreased the seed-setting rate of all the accessions, but the heat stress effects varied among accessions. Based on the decreases in seed-setting rate at high temperatures, N22 was the most tolerant, followed by AUS17, M9962, SONALEE and AUS16. Moreover, the reductions in seed-setting rate and yield under heat stress were more serious at the vegetative stage (45 d before heading) than at the booting stage (15 d before heading). In addition, heat stress also affected grain quality, especially by conferring chalkiness to most of the accessions, but SONALEE did not change much. The heat-tolerant accessions identified here and the phenotype protocols developed could be used in future genetic studies and breeding programmes focused on heat tolerance. Keywords: Heat tolerance, High temperature, Rice germplasm, Spikelet fertility, Seed-setting rate